Federalism and Judicialization of Public Health: How the Brazilian Supreme Court Solved a Federative Conflict under COVID-19’s Emergency. - Santos, Bruna Barboza Correia dos; Gomes Neto, Jose Mario Wanderley (Argumenta Journal Law, 2024)
Do federalist political categories matter in judicial decision-making during the pandemic? Under the health crisis, Brazilian federated entities (Union, States, Federal District, and Municipalities) had the challenge of working together. In March 2020, faced with the failure of the Union to exercise its natural leadership in defining the necessary social distancing measures (e.g., lockdown), a political party called the Brazilian Supreme Court to declare the constitutionality of the restriction measures unilaterally taken by States and Municipalities (ADI 6341). Concerning the resolution of federative litigation, a decision in favor of subnational entities denotes, at least temporarily, disruption with the tradition of the Brazilian Supreme Court. This research took a qualitative empirical approach (case study) to verify the influence of federative political categories (leadership, cooperation, and coordination) on the opinion of each Justice of the Brazilian Supreme Court when judging ADI 6341, regarding social distancing measures edited by subnational entities and therefore contrary to the interests of the federal government.